Physicochemical parameters of the longest back muscle of bulls of different breeds when using humic acids-based additives in their feeding - Skripin Petr; Svinarev Ivan; Gekhaev Badrudi; Chernyak Alexander; Gekhaev Rasul (BIO Web of Conferences)
The feed additive based on humic acids used in our studies in feeding Kalmyk, Kazakh White-headed and Aberdeen-Angus bulls convincingly proved its effect on the qualitative parameters of the longissimus dorsi muscle. In the experimental groups, the dominance of the area of the “muscle eye” was confirmed in the bulls of the VI experimental group (Aberdeen-Angus) by 10.62 cm2 (P < 0.01) relative to the V control group, the II experimental group (Kalmyk) - by 6.87 cm2 (P < 0.01), in relation to the control (I group), in the IV experimental group (Kazakh White-headed) - by 4.66 cm2 (P < 0.05) against the background of the control (II group). A decrease in moisture by 0.81% (P<0.05), 0.87% (P<0.05), 0.89% (P<0.05) and an increase in protein by 0.66 (P<0.05), 0.62 (P<0.05) and 0.75% (P<0.05) were recorded. The protein value increased due to the optimization of the amino acid composition. The quality of intramuscular fat increased due to an increase in unsaturated fatty acids. The process of meat maturation after slaughter of animals in the experimental groups was more effective. Monitoring the quality of meat products indicates its high nutritional and energy value. However, the best indicators were shown by bulls of the Aberdeen Angus and Kalmyk breeds.